The Trimeric Autotransporter Adhesin YadA of Yersinia enterocolitica Serotype O:9 Binds Glycan Moieties - Meuskens, Ina; Leva-Bueno, Juan; Millner, Paul; Schütz, Monika; Peyman, Sally A.; Linke, Dirk (Frontiers in Microbiology, 2022)
Yersinia adhesin A (YadA), is a key virulence factor of Yersinia enterocolitica and Yersinia pseudotuberculosis. YadA is a trimeric autotransporter adhesin, a class of adhesins that has been shown to enable many Gram-negative pathogens to adhere to/interact with host extracellular matrix proteins such as collagen, vitronectin and fibronectin. Here we show for the first time that YadA of Yersinia enterocolitica serotype O:9 not only interacts with proteinaceous surface molecules but can also attach directly to glycan moieties. We show that YadA from Yersinia enterocolitica serotype O:9 does not interact with the vitronectin protein itself but exclusively with its N-linked glycans. We also show that YadA can target other glycan moieties as found in e.g. heparin. So far, little is known about specific interactions between bacterial autotransporter adhesins and glycans. This could potentially lead to new antimicrobial treatment strategies as well as diagnostic applications.